(untitled) (Research, Society and Development, 2021)
Ethnobotanical collections are places where raw materials, products and artifacts, of vegetable origin partially or completely processed, are collected, and they have been treated, in Brazil, in the scope of biological collections. Thus, the study aims to consolidate the IFPA Ethnobotany Herbarium Collection (HIFPA). Species were categorized, representative families were presented and conservation status was verified. For this, a database with ethnobotanical information from the HIFPA was gathered in Microsoft Office Excel® 2010 format, and an active search was also carried out in the exsiccates deposited in the herbarium. The data were analyzed quantitatively regarding the utilitarian categories, also counting the representative families. The origin of the plants was consulted in Flora do Brasil 2020. The conservation status was verified by the base of the National Center for the Conservation of Flora. HIFPA currently has 1,850 exsiccates. Of this total, approximately 462 samples are part of the Ethnobotany Collection, representing 25% of the herbarium. The medicinal category was the most relevant, 390 exsiccates were verified, corresponding to 141 specific species, distributed in 57 families. Cedrela odorata was assessed as vulnerable in nature. The HIFPA Ethnobotany Collection is as rich and diverse as the other collections present at the Museu Paraense Emílio Goeldi and the State University of Pará. This research corroborates both the biocultural importance of the HIFPA Ethnobotany Collection and the potential that the collection offers for more scientific research.